2022
DOI: 10.1093/occmed/kqac024
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ occupational well-being in health and social care education

Abstract: Background The occupational well-being (OW) of educators can be defined as a balance between resources and workload factors as seen from four aspects of working life: (i) individual, (ii) working conditions, (iii) professional competence and (iv) work community. The research in this study examined the individual aspect as particular importance to the physical and mental workability of educators. Aims To study the individual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The International Labour Organization [ 20 ] considers occupational wellbeing as being constructed from all aspects of working life, including the workers’ perceptions of their work, the physical and mental working environment and the working community; considering these aspects will generate healthy, satisfied and engaged workers. The wellbeing was much studied in occupations such as physicians [ 19 ], nurses [ 18 ] and educators [ 21 ], and studies have shown that occupational wellbeing was influenced by leadership style, work environments, social support, employees' opportunities and work relationships [ 18 , 22 , 23 ]. Previous studies have mostly focused on the impacts of work-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…The International Labour Organization [ 20 ] considers occupational wellbeing as being constructed from all aspects of working life, including the workers’ perceptions of their work, the physical and mental working environment and the working community; considering these aspects will generate healthy, satisfied and engaged workers. The wellbeing was much studied in occupations such as physicians [ 19 ], nurses [ 18 ] and educators [ 21 ], and studies have shown that occupational wellbeing was influenced by leadership style, work environments, social support, employees' opportunities and work relationships [ 18 , 22 , 23 ]. Previous studies have mostly focused on the impacts of work-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the overall E27 (eg, collegiality); (3) working conditions (eg, physical factors); and (4) professional competence (eg, pedagogical skills). 2,8 The focus of this study is in the first of these 4 aspects, the personal resource-workload-balance.…”
Section: Introductionmentioning
confidence: 99%
“…10 Self-Help INtervention for Educators (SHINE) was created to be applicable to the daily working life of educators working in nursing education needing better resource-workload-balance. 2,3 There are 4 resourceworkload-balance promoting components implemented in SHINE: (1) physical activity at work; (2) recovery activities at work; (3) self-regulation development activities at work; and (4) workplace support for personal resources promoting activities at work. The aim of SHINE is to promote the resource-workload-balance (primary outcome); its associated factors (overall OW and general well-being [GW], secondary outcomes); and its promotive factors (physical activity, recovery experiences, self-regulation, and workplace support, condition outcomes) (see Supplemental Digital Content, Figure 1, available at: http://links.lww.com/NE/B363).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations